A review of captive flamingo (Phoenicopteridae) welfare: a synthesis of current knowledge and future directions. Issue 1 (9th January 2014) - Rose, P. E.; Croft, D. P.; Lee, R.
<x xml:space="preserve">Abstract</x> Flamingos are ubiquitous captive species (potentially the world's most commonly kept zoo bird) that have long lifespans and unique breeding cycles. In‐depth research into the links between provision (enclosure, husbandry), behavioural performance (reflecting internal motivation) and perceived welfare state (from behavioural cues) can inform management for good welfare over the many decades of a bird's life, and benefit reproductive output. Here, the published literature on flamingo husbandry is reviewed, with reference to our current understanding of flamingo behaviour in the wild. Evaluation of whole‐flock time budgets and assessment of behavioural diversity can highlight any deviation from a norm. Several published works suggest ways of improving breeding success in captive flamingos by re‐evaluating husbandry routines as well as highlighting minimum numbers of birds per flock for 'good welfare'. Research has shown that some aspects of zoo‐flamingo activity can match that of wild birds. Further examination of specific behaviour patterns, as well as the motivations for these, would allow for evidence‐based enclosure design and provision of species‐specific behavioural husbandry. Future research topics covering social support, foraging activity and developing a definition of 'positive welfare activity' would further enhance zoo management practices for these birds.